Acceptance and Usability of Complex Medical Systems: A Study with Radiology Professionals - Silva, Fábio Ap. Cândido da; Freire, André Pimenta; Pereira, Marluce Rodrigues (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the Web, 2024)
The increasing demand for imaging tests has made radiology information systems crucial in medical practice, especially those based on web technology. These systems include Picture Archiving and Communication System (PACS), Radiology Information Systems (RIS), and Hospital Information System (HIS), generate and manipulate images through specialized software. To operate this complex software, require attention to detail and image manipulation techniques for accurate diagnoses. Usability issues in medical image manipulation software, given the process of adapting to new software and complex tasks, can result in inaccurate diagnoses with clinical impact. This is a qualitative study, which is based on the work routines of radiology professionals, focusing on issues of cognitive learning, interaction, and usability with radiology software. Moderate usability tests with radiology technicians were conducted to identify the difficulties and challenges they encounter while using medical image manipulation software. The analysis identified 64 problems grouped into 20 categories and organized under Visual Presentation, Content, Information Architecture, and Interactivity. The paper emphasizes violated heuristics and describes how these problem categories impact users in their medical activities and their influence on the clinical process. The obtained results provide insights to enhance usability practices and recommendations, aiming to support the development systems used in radiology practice.